Urban green space disparities: Implications of environmental injustice for public health - Bressane, Adriano [UNESP]; Cunha Pinto, Joao Pedro da [UNESP]; Castro Medeiros, Líliam César de [UNESP] (Elsevier, 2024)
Urban Green Spaces (UGS) offer extensive benefits, yet their distribution reveals significant socioeconomic disparities. Despite the growing body of research, there is a gap in understanding the spatial equity of greenspace, especially in the Global South. This gap extends to the association between UGS and public health in the context of low-income countries. This study delves into the socioeconomic-green relationships within the Brazilian metropolitan areas’ context. The research comprised a survey of 2597 participants, assessing their sociodemographic profiles, accessibility and suitability of UGS, frequency and duration of visits to UGS, and the impact on their mental well-being (via DASS-21). Welch's ANOVA and Pearson's χ² tests revealed significant sociodemographic disparities in UGS accessibility and in well-being. Gender, age, and marital status were associated with mental health. The study found that proximity and suitability of UGS significantly impacted mental health, with well-maintained spaces linked to lower mental distress. No direct correlation was found between income levels and proximity to UGS, however, disparities in access to suitable green spaces were evident. Findings highlight the need for tailored urban planning and policies ensuring equitable access to quality UGS. Strategies should consider the characteristics of neighborhoods and involve community participation to address environmental justice effectively.
Keywords: Disparities; Environmental justice; Public health; Urban green spaces